The Nepali Army’s Contribution to Nation Building - Bhat, Anand Singh (Unity Journal, 2023)
The nation-building process involves various approaches such as democratization, inclusiveness, promotion of nationalism, unification, internal restructuring for cultural promotion, and developmental activities to build the loyalty of peripheral people towards the centre. The Nepali State has been employing the Nepali Army as a strategic means to build the Nepali Nation. However, how the Nepali Army has contributed to nation building since its establishment is area that is under-explored. Hence, this article focuses on some of these important strategies using nation-building theories. It is argued that the Nepali army has been significantly contributing to nation building through territorial unification, internal restructuring, and developmental activities in support of nation building since the unification of Modern Nepal. This study initially discusses the contribution of the Nepali Army in territorial unification by conquering principality states and internal restructuring through consolidation of administration and promotion of nationalism. Thereafter, it delves into the integration of local folk cultures to build the Nepali Culture and inscription symbols. Finally, the article analyses developmental works in support of nation building that connects peripheral remote places with the capital city Kathmandu. A conceptual framework based on Saunders' Research Onion Peeled Method is applied with purposive sampling and document study from John Galtung and Stein Rokkan's theoretical lenses has been applieed. The article finds that the Nepali Army initially contributed to the nation building through a unification campaign before consolidating nationalism in the 1950. Further, the Nepali Army continued participating in development activities to link the periphery to the center.